Hysteresis in turbulent pipe flow relating to the modified hagen-poiseuille relation and to observed velocity and pressure profiles - Remolona, Miguel Francisco M. (2011)
Recent studies by Murial, et al. {[5] have shown that hysteresis occurs in turbulent pipe flow of gases such that the flow regularly oscillates between a high energy and a low-energy region. This oscillation is not present at low pressure gradients characterized by laminar flow. They have also shown a proportionally relation between the logarithm of flow rate and the logarithm of driving force, pressure, for gasses where the proportionality constant, n, is specie-dependent. This study conducted a correlation test on the previously identified values of the proportionality constant, n. The value of n exhibited a good linear and quadratic relation with respect to molecular weight and a good quadratic relation with respect to first excitation energy. This study also tested that the proportinality relation is valid for both the high-energy and low-energy region of flow. The values of n were obtained for argon, 0.252 to 0.390 and 0.434 to 0.926, nitrogen, 0.428 to 0.864, xenon, 0.322 to 0.349, krypton, 0.292 to 0.336, and neon, 0.221 to 0.295. These values of n obtained showed moderately acceptable correlation.